Isolation, identification and characteristics of yeasts from natural fermentation of Citrus macrocarpa - MA Zewei, ZHANG Hongjian, LIU Shuaiguang, LI Rongli, HUANG Huan, ZHENG Lianhe (Zhongguo niangzao)
To identify microorganisms suitable for fermenting Citrus microcarpa whole fruit pulp under high acid conditions, yeast was screened from the natural fermentation liquid of C. microcarpa whole fruit pulp by traditional isolation and purification methods, and the isolated strains were identified by morphological observation and ITS sequencing. The growth performance and tolerance of the strains to temperature, pH and glucose concentration were evaluated. The inhibition rate of total phenol, total flavone, α-glucosidase and antioxidant activity of whole fruit pulp of the isolated strains were compared before and after pure fermentation. The results showed that three yeasts (Y1, Y14, and Y15) were isolated from the natural fermentation of C. microcarpa whole pulp. The strain Y1 was identified as Pichia terricola, strains Y14 and Y15 were identified as Hanseniaspora opuntiae. These yeasts exhibited tolerance towards environmental conditions such as 35 ℃, glucose mass concentration 400 g/L, and pH 2.0. The total phenols, total flavonoids, DPPH free radical and ABTS free radical scavenging rates, copper reducing ability and α-glucosidase inhibition rates of purebred strains Y1, Y14 and Y15 were increased by 20.65%, 87.15%, 20.45%, 43.94%, 34.08%; 20.34%, 19.22%, 51.90%, 18.31%, 39.39%, 25.94%, 24.82%; 19.97%, 70.01%, 22.92%, 34.85%, 30.85%, 13.53%, respectively.